2014
DOI: 10.5039/agraria.v9i2a3885
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do desenvolvimento e reservas energéticas de larvas de Rhynchophorus palmarum (Coleoptera:Curculionidae) em diferentes dietas

Abstract: A cultura das palmáceas é de grande importância, uma vez que faz parte do ecossistema agrícola produtivo, fornecendo produtos e subprodutos, como óleo, gorduras, minerais, vitaminas essenciais e frutos frescos gerando rendas para as populações. O Rhynchophorus palmarum é uma das principais pragas das culturas sendo vetor do nematoide Bursaphelenchus cocophilus, agente causal da doença do Anel vermelho. Não existem métodos eficientes e ecologicamente viáveis que possam reduzir significativamente os danos e a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…() reported that enzymes in the glycolysis pathway, including PYK, are necessary for embryonic muscle development. A related study also reports that PYK activity increased during early embryogenesis in the beetle Rhynchophorus palmarum (Santana et al., ). We infer that PYK activities and energy metabolism are necessary processes in insect embryonic development.…”
Section: Introductionmentioning
confidence: 76%
“…() reported that enzymes in the glycolysis pathway, including PYK, are necessary for embryonic muscle development. A related study also reports that PYK activity increased during early embryogenesis in the beetle Rhynchophorus palmarum (Santana et al., ). We infer that PYK activities and energy metabolism are necessary processes in insect embryonic development.…”
Section: Introductionmentioning
confidence: 76%
“…La correlación positiva observada entre el contenido de carbohidratos, energía de las dietas y el contenido lipídico de las larvas de R. palmarum, puede explicarse debido a que el metabolismo de las larvas les permite almacenar la energía calórica en la forma de compuestos lipídicos, especialmente triglicéridos, sintetizados a partir de los nutrientes disponibles en las dietas suministradas, especialmente los carbohidratos (SANTANA et al, 2014). Según Angel-Dapa et al (2010), en los insectos, los lípidos juegan un papel clave en la maximización de la tasa de huevos eclosionados (fecundidad), crecimiento larvario y supervivencia.…”
Section: Resultados Y Discucionesunclassified
“…Wegener et al [21] found that insect survival decreased with the decrease of trehalase activity. In addition, The embryo development of insects was affected by pyruvate kinase and regulated by juvenile and molting hormones [22][23][24]. In insects, juvenile and molting hormones were present at minute levels and were continuously synthesized and degraded.…”
Section: Introductionmentioning
confidence: 99%